Study On Breeding Management Practices Of Buffaloes In Relationship With Selected Traits Of Respondents In Jaipur District Of Rajasthan (India) - Manohar, D.S.; Bais, Basant; Goswami, S.C.; Jhirwal, A.K.; Choudhary , D. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A field survey was conducted to collect the first hand information on the breeding management practices of buffalo farmers in Jaipur district of Rajasthan. Only 30 per cent of the respondents adopted A.I. Majority (82.50 per cent) of the respondents used crossbred ( Khumbi,) and a small fraction of indigenous bull (17.50 per cent) for natural service of their buffaloes. 62.50 per cent of the respondents practiced pregnancy diagnosis of their buffaloes. The size of herd was found significantly (p<0.01) correlated with all the breeding management practices namely, breeding method, type of breeding bull, heat detection, pregnancy diagnosis, treatment of repeat breeders etc. Education was significantly (p<0.05)correlated with all the breeding management practices.